Deposit insurance, financial liberalization and the problem of moral hazard - Lalta, Stanley (ISER MonaJA, 1993)
Examines the possibilities offered by deposit insurance schemes to improve efficiency and confidence in the financial system in particular to protect depositors in a context of widespread financial liberalization.